Longitudinally extensive vasogenic edema following spinal cord infarction. Issue 5 (11th July 2018) - Gondo, Takashi; Kurihara, Masanori; Sugiyama, Yusuke; Mano, Tatsuo; Mori, Harushi; Hayashi, Toshihiro; Tsuji, Shoji
Abstract: Although transient lesion expansion has been reported after spinal cord infarction, longitudinally extensive lesion expanding more than several vertebral segments is extremely rare. We report a 45‐year‐old man having spinal cord infarction with subsequent longitudinally extensive lesion expansion on magnetic resonance imaging (MRI) 10 days after the infarction. The length of T2 hyperintense lesion was four vertebral segments on initial MRI but enlarged to span 12 vertebral segments on subsequent MRI, with Lhermitte's sign, but otherwise without neurological deterioration. The expanded lesion extended beyond the anterior spinal artery region with high apparent diffusion coefficient value in the acute phase but improved within 10 days after starting cervical collar, suggesting that lesion expansion was due to vasogenic edema. This case illustrates that transient longitudinal lesion expansion accompanied by spinal cord infarction can reach lengths of up to 12 vertebral segments. Caution should be exercised while interpreting MRI findings to avoid excessive treatment or secondary damage.